2020
DOI: 10.5194/jsss-9-283-2020
|View full text |Cite
|
Sign up to set email alerts
|

Siloxane treatment of metal oxide semiconductor gas sensors in temperature-cycled operation – sensitivity and selectivity

Abstract: Abstract. The impact of a hexamethyldisiloxane (HMDSO) treatment on the response of doped SnO2 sensors is investigated for acetone, carbon monoxide and hydrogen. The sensor was operated in temperature cycles based on the DSR concept (differential surface reduction). According to this concept, the rate constants for the reduction and oxidation of the surface after fast temperature changes can be evaluated and used for quantification of reducing gases as well as quantification and compensation of sensor poisonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…SGP30 multilayer MOS sensors (four sensitive layers on one hotplate, Sensirion AG, Stäfa, Switzerland) were used for this study. One sensor device was installed as delivered and another one was pre-treated with Octamethylcyclotetrasiloxane at 2 ppm over 18 h yielding a H 2 selective sensor (compare [26,28]). The temperature cycle is specifically designed to achieve high sensitivity and selectivity by using the differential surface reduction (DSR) method, which is described in detail in previous publications [32][33][34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SGP30 multilayer MOS sensors (four sensitive layers on one hotplate, Sensirion AG, Stäfa, Switzerland) were used for this study. One sensor device was installed as delivered and another one was pre-treated with Octamethylcyclotetrasiloxane at 2 ppm over 18 h yielding a H 2 selective sensor (compare [26,28]). The temperature cycle is specifically designed to achieve high sensitivity and selectivity by using the differential surface reduction (DSR) method, which is described in detail in previous publications [32][33][34].…”
Section: Methodsmentioning
confidence: 99%
“…In this manuscript we present an extended field-study over two months inside an office at the university with a focus on H 2 to get a better overall idea on the topic of H 2 in indoor air-as interferent and as target gas. Two approaches for achieving selective H 2 quantification were combined: TCO followed by pattern analysis with machine learning (ML) algorithms [10,11] and a pre-treatment of the sensitive layer with siloxane, which in other circumstances is called poisoning since it deteriorates all sensitivities except for H 2 [27][28][29][30][31]. The performance of the sensor signals is validated by release tests and a GC with reducing compound photometer (RCP) detector (Peak Performer 1, Peak Laboratories Inc., Mountain View, CA, USA), which to our knowledge is the only analytical device for online measurement of hydrogen with ppb-level resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile organic silicon compounds (VOSCs) are widely used in consumer goods such as electronics, furniture, healthcare, pharmaceuticals, cosmetics, and cookware, 93 leading to significantly higher concentrations indoors than outdoors. [94][95][96] Over the last decades, a great deal of effort has been invested in identifying Si-impurity sources and developing means for avoiding contamination. For example, van Berkel et al prevented Si-poisoning in oxygen permeation membrane measurements by avoiding VOSC containing grease in the manual valves of the experimental setup.…”
Section: Silica As a Potential Poisonmentioning
confidence: 99%
“…Williams and Pratt, and Schultealbert et al, both found that exposure to VOSCs deactivate different surface sites on SnO2 and at varying rates (Figure 10a). 95,96 The transient response to all gases slows down as a result of Si poisoning, but the active sites for hydrogen appear to be deactivated to a lesser degree than those for the other gases, (Figure 10b). The authors argue that the high selectivity, and even increased steady state response to hydrogen, results from the fact that the readsorption of oxygen is more strongly hindered by the adsorption of VOSCs than the reduction by hydrogen.…”
Section: Oxygen Reduction and Exchange Reactionsmentioning
confidence: 99%
See 1 more Smart Citation